Regional brain volume reductions in major depressive disorder and bipolar disorder: An analysis by voxel‐based morphometry. (9th November 2018) - Niida, Richi; Yamagata, Bun; Matsuda, Hiroshi; Niida, Akira; Uechi, Akihiko; Kito, Shinsuke; Mimura, Masaru
Abstract : Objectives: The present study investigated the usefulness of evaluating the existence of volume reduction in brain regions using voxel‐based morphometry (VBM) to dissociate major depressive disorder (MDD) from bipolar disorder (BD). Methods/Design: This study enrolled 92 individuals with MDD, 32 individuals with BD, and 43 healthy controls (HCs). We focused on gray matter volume (GMV) of the subgenual anterior cingulate cortex (sgACC), subcallosal area (SCA), and hippocampus. The degree of volume reduction in these brain regions was calculated as the z score, and the differences of z scores in these regions were investigated among the MDD, BD, and HC groups. We then performed a receiver operating characteristic curve analysis to dissociate the individuals with MDD and BD from the HCs based on the z scores in the GMV of these brain regions. Results: While there were no significant differences in the z scores of the hippocampus among the three groups, the z score of the sgACC was significantly higher in the MDD group than in the BD and HC groups, and the SCA z score was significantly higher in the MDD and BD groups than in the HC group. Conclusions: Our findings suggest that VBM evaluation of GMV reduction in the sgACC may be useful as an objective adjunctive tool to distinguish between MDD and BD.